Efficacy and safety of regorafenib for the treatment of metastatic colorectal cancer in routine clinical practice: results from a Spanish hospital - Sotoca Rubio, Pilar; Barrill Corpa, Ana María; Alia Navarro, Víctor; Pérez de Aguado Rodríguez, Patricia; Moreno Doval, Jaime; Calvo Pérez, Juan Carlos; Guerrero Serrano, Patricia; García Merino, Carlos; García de Quevedo Suero, Coral; Fernández-Fradejas, Jorge; Serrano Domingo, Juan José; Martínez Delfrade, Íñigo; et al. (Frontiers in Oncology, 2024)
IntroductionRegorafenib is indicated as treatment in third-line and beyond in patients with metastatic colorectal cancer.Methods This is a retrospective study of a cohort of patients with mCRC treated with regorafenib in Hospital Universitario Ramón y Cajal, in Madrid, Spain.ResultsWith the aim to assess the efficacy and safety of regorafenib, 91 patients treated between 2013 and 2023 were included. Only 1.1% of patients achieved disease control. Median progression free survival was 2.40 months and median overall survival was 4.76 months. The most frequent adverse events were fatigue and hand-foot skin reaction (59.34% and 28.57%, respectively).DiscussionOur results confirm the safety of regorafenib as treatment of mCRC in real clinical practice. Although our population is less pretreated than in the CORRECT trial, our disease control rate was inferior. This difference may be due to a worse baseline status and a high percentage of hepatic disease showed in our patients.